2021
DOI: 10.1111/1755-0998.13546
|View full text |Cite
|
Sign up to set email alerts
|

Assessing candidate DNA barcodes for Chinese and internationally traded timber species

Abstract: Accurate identification of species from timber is an essential step to help control illegal logging and forest loss. However, current approaches to timber identification based on morphological and anatomical characteristics have limited species resolution. DNA barcoding is a proven tool for plant species identification, but there is a need to build reliable reference data across broad taxonomic and spatial scales. Here, we construct a species barcoding library consisting of 1550 taxonomically diverse timber sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 134 publications
0
10
0
Order By: Relevance
“…Furthermore, the China Plant BOL Group recommended that the nuclear internal transcribed spacer (nrITS) be incorporated into the core plant barcode (Li et al, 2011). There are numerous successful cases of using traditional standard DNA barcodes (including the multilocus combination of plastid rbc L + mat K + trn H‐ and nrITS) or other specific barcodes (Bruni et al, 2010; Hu et al, 2022; Liu et al, 2011, 2018; Xu et al, 2018). However, other research has shown that traditional standard DNA barcodes have tremendous limitations in species discrimination, primarily attributed to a lack of variation in many taxa, especially in evolutionarily young and rapidly radiated taxa (Spooner, 2009; van Velzen et al, 2012; Yan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the China Plant BOL Group recommended that the nuclear internal transcribed spacer (nrITS) be incorporated into the core plant barcode (Li et al, 2011). There are numerous successful cases of using traditional standard DNA barcodes (including the multilocus combination of plastid rbc L + mat K + trn H‐ and nrITS) or other specific barcodes (Bruni et al, 2010; Hu et al, 2022; Liu et al, 2011, 2018; Xu et al, 2018). However, other research has shown that traditional standard DNA barcodes have tremendous limitations in species discrimination, primarily attributed to a lack of variation in many taxa, especially in evolutionarily young and rapidly radiated taxa (Spooner, 2009; van Velzen et al, 2012; Yan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the mitochondrial gene cytochrome oxidase I ( COI ) has been proven to be an ideal DNA barcode for animals (Burns et al, 2008; Kerr et al, 2007; Kim et al, 2012), whereas this DNA region is not suitable for plant identification due to the low substitution rates of plant mitochondrial DNA (Cho et al, 2004; Duminil, 2014; Kress et al, 2005). Alternatively, plastid sequences ( rbcL and matK ) and the internal transcribed spacer (ITS) of nuclear ribosomal DNA (nrDNA) have been recommended as core barcodes for plants, and plastid sequences ( trnH‐psbA and trnL ‐F) have been recommended as supplementary barcodes (CBOL Plant Working Group, 2009; Chase et al, 2007; Hollingsworth et al, 2011; Hu et al, 2022; Kress et al, 2009; Lahaye et al, 2008; Li et al, 2009; Li, Gao, et al, 2011; Li, Liu, et al, 2011; Tonti‐Filippini et al, 2017; Vijayan et al, 2009; Worthy et al, 2022). The application of DNA barcoding has been successfully used in the problem of species identification in a large number of taxa (e.g., Giudicelli et al, 2015; Gogoi & Bhau, 2018; Liu et al, 2011, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The arid region covers nearly 25% of the territory in China. However, the DNA barcode reference libraries in China are concentrated primarily in southern biodiversity‐rich areas, for example subtropical forests (Liu et al, 2015), mangrove forests (Mao et al, 2021) and timber species (Hu et al, 2022), with limited DNA barcode data for northwestern arid regions.…”
Section: Discussionmentioning
confidence: 99%
“…(i) Barcoding gap method: intra‐ and interspecific genetic distances were calculated for each barcode ( rbcL , matK , ITS and ITS2) separately by using “DistanceMatrix” in the R (R Core Team, 2019) package decipher (Wright, 2016). Barcode gaps existed for species with lower maximum intraspecific distances than with minimum interspecific distances (Gill et al, 2019; Hu et al, 2022). (ii) All‐to‐all blast search method (Kelly et al, 2011): based on blast version 2.10.1+ all barcode sequences served as both reference and query databases.…”
Section: Methodsmentioning
confidence: 99%